APLIKASI MONITORING KADAR TANAH, KADAR AIR DAN KELEMBAPAN TANAH LADANG JAGUNG MELALUI WEB BERBASIS MIKROKONTROLER - Emiliyana Varida Sholehah; Muhammad Rusdi; Muhammad Edya Rosadi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Corn is included in the category of fruit that farmers have planted since ancient times using the instinct method in determining the soil content of corn plants. Along with the development of the times, farmers used a soil meter to measure soil pH, humidity, and lighting. However, there are areas for improvement in the microcontroller in the form of data that needs to be stored. So farmers need calculations to measure soil pH, water pH, and humidity. Monitoring is carried out by storing data to continuously know the level of its value. Based on these problems, through this research, an application for monitoring soil content, moisture content and soil moisture for corn fields through a microcontroller-based web was made, and data collection was carried out in the farmer's field in Batu Ampar village covering an area of 10,000 meters2. The microcontroller's data follows field conditions, the results of calculations using web. At the same time, the web page can be viewed by farmers. Besides being able to monitor soil and water, farmers can see the location of the soil whose data was taken on the free user maps page and choose a marker, then the name of the place, address, date and time of the pH results have been monitored will appear. For further research development, the authors suggest minimizing the cost of making a microcontroller, adding sensors, and hosting web pages so that they can be viewed in the form of a mobile web application.